Tingkat Keberhasilan Inseminasi Buatan (IB) Pada Sapi Di Kelompok Ternak Sumber Sapi Mulya Kecamatan Babakan Kabupaten Cirebon Jawa Barat Indonesia: Success Rate of Artificial Insemination (IB) in Cattle in the Mulya Cattle Source Livestock Group, Babakan District, Cirebon Regency, West Java, Indonesia - Perwitasari, Fitri Dian; Al Kurnia, Dyanovita Al Kurnia; Daning, Dewi Ratih Ayu; Bastoni, Bastoni; Arisandi, Bayu (Jurnal Riset Agribisnis dan Peternakan, 2025)
Efforts to increase the beef cattle population are needed to support the increase in demand for livestock products. The government has achieved meat self-sufficiency by increasing the beef cattle population through the UPSUS SIWAB program, one of which is Artificial Insemination (IB). This study aims to determine the success rate of artificial insemination in the breeding group of noble cattle in Sumber lor village, Babakan district, Cirebon regency reviewed from Service per Conception (S/C), Conception Rate (CR), and Calving Interval (CI). The data used are primary data through interviews with farmers and data from the Cirebon Regency Agriculture Office in 2022-2024. The results of the study show that the S/C value in 2022 is 1.91, in 2023 it is 1.98, and in 2024 it is 1.86, the CR value in 2022 is 61.36%, in 2023 it is 56.52% and in 2024 it is 66.67%, and the majority CI value is 60.38% in 12-15 months. The conclusion of the research results is that the success rate of artificial insemination in the noble cattle source group in Sumber lor village, Babakan district, Cirebon regency has been running well.